The last crusade : the epic voyages of Vasco da Gama - Cliff, Nigel author; Cliff, Nigel. Holy war, how Vasco da Gama's epic voyages turned the tide in a centuries-old clash of civilizations. (New York, N.Y. : Harper Perennial/HarperCollins Pub., 2012)
Includes bibliographical references (p. [512]-526) and index.